7 - Participants’ evaluation of the land reform programme in Rwanda’s Southern Province - Jean de Dieu Dushimimana; Johan Zaaiman (African Sociological Review, 2018)
Land reform is a state-initiated process that aims to redistribute land in such a way that the poor and vulnerable can benefit. To overcome previous socio-political and economic induced inequalities, several countries embarked on land reform to help improve the quality of life of inhabitants and redress inequality. The land reform implemented in 2006 in Rwanda was a unique programme due to the specific history of this country. This article presents participants’ evaluation in 2014 on land reform. Through a survey, interviews and focus groups, role- players in land reform within the Southern Province of Rwanda indicated that the reform was advantageous because of the security and benefits of ownership it provided and the cooperation it ensured. More state support and agricultural freedom were, however, requested.